A cabinet secretary looks back - Deshmukh, B. G. (Bhalchandra Gopal), 1929- (HarperCollins Publishers India a joint venture with India Today Group, 2004)
Service memoirs of Bhalchandra Gopal Deshmukh, b. 1929, a former Indian cabinet secretary; includes autobiographical references.